(untitled) (Revista Electrónica REDINE, 2020)
Thinking about sports training remotely implies the knowledge and imperative mastery of the foundations and principles of the Distance Learning as an innovative educational modality, which proposes a new vision of helping in the sports training process, when the dynamics of sport itself warrants the distance between the coach and the athlete. In addition, within this context, the proper use of information and communication technologies (ICT) represents a real challenge to design, apply and model resources, strategies and environments sufficiently adequate to guide and complement the sports training process, beyond the traditional face-to-face modality. This documentary work as the state of the art aims to open spaces for reflection and debate to propose conceptual approaches to Distance Sports Training (DST) from the review and analysis of the refereed literature related to these topics and from there, to discern about a conscious professional practice by of the agents that link to the integral formation of the athlete.